Inclusiveness of contract farming along the vertical coordination continuum: Evidence from the Vietnamese rice sector - Ba, Hélène A.; de Mey, Yann; Thoron, Sylvie; Demont, Matty (Elsevier, 2019)
The Vietnamese government is currently attempting to upgrade rice value chains in the Mekong River Delta by encouraging (i) vertical coordination between exporters and farmers through contract farming, and (ii) horizontal coordination among farmers through the “small farmers, large field” program. Previous studies on the determinants of contract farming participation assume that firms offer only a single contract type, whereas in reality, farmers may face a continuum of exclusive contract options. Devising correct and targeted policies for fostering contract inclusiveness hence crucially hinges on deploying correct econometric specification of the decision to participate in contract farming. We model contract farming participation and intensity in four different ways along the vertical coordination continuum: as a discrete, categorical, ordered, and continuous choice. We find that older, smaller and horizontally coordinated farmers with higher levels of trust in buyers tend to secure higher levels of buyer investment through increased vertical coordination. In contrast with the common finding in the literature that contract participation is biased towards larger farms, our findings from Vietnam suggest that the scale bias of contract farming could be successfully relaxed through horizontal coordination and even reversed under increasing levels of vertical coordination as smaller farmers are found to secure higher levels of buyer investment. These findings highlight the role both policies can play in fostering inclusiveness of contract farming in rice value chain upgrading in Vietnam